2006
DOI: 10.3748/wjg.v12.i37.5951
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gastric emptying is associated with pylorus-preserving but not classical Whipple pancreaticoduodenectomy: A review of the literature and critical reappraisal of the implicated pathomechanism

Abstract: Pylorus-preserving pancreaticoduodenectomy (PPPD) is nowadays considered the treatment of choice for periampullary tumors, namely carcinoma of the head, neck, or uncinate process of the pancreas, the ampulla of Vater, distal common bile duct or carcinoma of the peri-Vaterian duodenum. Delayed gastric emptying (DGE) comprises one of the most troublesome complications of this procedure. A search of the literature using Pubmed/Medline was performed to identify clinical trials examining the incidence rate of DGE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 93 publications
(97 reference statements)
1
41
0
6
Order By: Relevance
“…However, the majority of recent clinical trials found no signifi cant difference in the incidence of DGE between PD and PPPD. 29 The surgical procedure that is neutrally positioned between conventional PD and PPPD is SSPPD. Although the pyloric ring is removed in this procedure, most of the stomach is preserved.…”
Section: Pancreatoduodenectomymentioning
confidence: 99%
“…However, the majority of recent clinical trials found no signifi cant difference in the incidence of DGE between PD and PPPD. 29 The surgical procedure that is neutrally positioned between conventional PD and PPPD is SSPPD. Although the pyloric ring is removed in this procedure, most of the stomach is preserved.…”
Section: Pancreatoduodenectomymentioning
confidence: 99%
“…[1][2][3][4][5] Recently, several large-volume randomized control studies 6-10 and meta-analysis 11,12 comparing PD and PPPD have been reported with a conclusion that there is no significant difference in the oncologic outcome and quality of life between the two operative methods. However, the occurrence of delayed gastric emptying (DGE) in the postoperative course after PDs is a controversial object.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The mechanism of DGE is still unclear, and several causal mechanisms for DGE, such as interrupted gastrointestinal neural connection, local ischemia, loss of gastrointestinal hormone production, anatomical position, intra-abdominal infection, undetected anastomotic leakage or pancreatitis, and pylorus preservation have been proposed and discussed. 4 Subtotal stomach-preserving pancreaticoduodenectomy (SSPPD) has been performed in Japan since the 1990s. In standard PD, usually 30-40% of the distal stomach is resected, while in SSPPD, the stomach is separated at the 2-to 3-cm proximal side of the pylorus ring and most part of the stomach is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…. Interessanterweise wurde dieses Phä-nomen bereits in früheren Jahren in bis zu 70% nach pyloruserhaltender Pankreaskopfresektion beschrieben, was oftmals eine verlängerte Hospitalisation erforderte [19]. Verschiedene Theorien wurden in Feld geführt (1.…”
Section: Introductionunclassified
“…Lage der Duodenojejunostomie [antekolisch/retrokolisch], 2. gastrointestinale Hormonstörung [Motilin], 3. partielle Ischämie durch Resektion der A. gastrica dextra), von denen aber keine wirklich konsensfähig ist [8]. Fakt ist jedoch, dass eine verzögerte Magenentleerung in aktuellen Arbeiten mit geringerer Inzidenz (25-30%) und unabhän-gig vom Operationstyp berichtet wird [19,6]. Ob dies auf eine intraoperativ durchgeführte Dilatation des Pylorus (auf 29 mm) zurückzuführen ist, wie von Fisher et al kürzlich vorgeschlagen [8], bleibt unbeantwortet.…”
Section: Introductionunclassified